Form and Structure of Music in the Tidi Lo Polopalo Dance from the Gorontalo Community - Sri Rahayu Hidayat Miu; Aris Setiawan (Gondang: Jurnal Seni dan Budaya, 2026)
Tidi Lo Polopalo is a traditional dance performed during traditional wedding ceremonies, commonly referred to as 'Hui Mopotilandahu.' This dance symbolizes the refined character and grace of a woman, her hospitality, as well as the duties and responsibilities she will assume after marriage. This dance cannot exist without its accompanying music; in this context, music is considered essential in strengthening the identity of the dance, which serves to represent the essence of womanhood in Gorontalo. he musical accompaniment of the Tidi Lo Polopalo dance is not merely a form of entertainment in traditional ceremonies; rather, it serves as a manifestation of cultural expression rooted in specific values. Within the performance, the music acts as a universal language that transcends words. This study aims to analyze the form and structure of the musical accompaniment in the Tidi Lo Polopalo dance within the Gorontalo community. This study employs a qualitative method, incorporating interviews, literature reviews, and direct observation. The research utilizes the concepts of form and structure to analyze a vocal or musical composition, which conveys the creator's thoughts and emotions through musical elements specifically tempo, rhythm, harmony, and expression as a unified whole. The results of this study indicate that the form and structure of the music in the Tidi Lo Polopalo dance reflect the aesthetic dimensions of sound within the Gorontalo community. Consequently, the presence of this music is essential in accompanying the Tidi Lo Polopalo dance for the people of Gorontalo.